2012 IEEE Fifth International Conference on Software Testing, Verification and Validation 2012
DOI: 10.1109/icst.2012.124
|View full text |Cite
|
Sign up to set email alerts
|

Towards Automated Anomaly Report Assignment in Large Complex Systems Using Stacked Generalization

Abstract: Maintenance costs can be substantial for organizations with very large and complex software systems. This paper describes research for reducing anomaly report turnaround time which, if successful, would contribute to reducing maintenance costs and at the same time maintaining a good customer perception. Specifically, we are addressing the problem of the manual, laborious, and inaccurate process of assigning anomaly reports to the correct design teams. In large organizations with complex systems this is particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 14 publications
(17 reference statements)
2
25
0
Order By: Relevance
“…Previous work report that bug tossing is frequent in large projects; 25% of bug reports are reassigned in the Eclipse Platform project (Anvik and Murphy, 2011) and over 90% of the xed bugs in both the Eclipse Platform project and in projects in the Mozilla foundation have been reassigned at least once (Bhattacharya et al, 2012). Moreover, we have previously highlighted the same phenomenon in large-scale maintenance at Ericsson (Jonsson et al, 2012).…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Previous work report that bug tossing is frequent in large projects; 25% of bug reports are reassigned in the Eclipse Platform project (Anvik and Murphy, 2011) and over 90% of the xed bugs in both the Eclipse Platform project and in projects in the Mozilla foundation have been reassigned at least once (Bhattacharya et al, 2012). Moreover, we have previously highlighted the same phenomenon in large-scale maintenance at Ericsson (Jonsson et al, 2012).…”
Section: Introductionsupporting
confidence: 58%
“…In the eld of software engineering, applications of SG include predicting the numbers of remaining defects in black-box testing (Li et al, 2011), and malware detection in smartphones (Amamra et al, 2012). In a previous pilot study, we initially evaluated using SG for bug assignment with promising results (Jonsson et al, 2012). Building on our previous work, this paper constitutes a deeper study using bug reports from dierent proprietary contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to what was pointed out in the study above, users and managers at our organization question why they should trust a "blackbox" ML system 1 . The problem concerning uncertainty in the results from the tool manifests itself when a user is employing a fault localization tool and is getting a recommendation, but the tool does not offer any measure of the confidence in the recommendation.…”
Section: Introductionsupporting
confidence: 58%
“…Efficiency in the bug handling process is essential, and previous research [1], [2], [3], [4], [5] has shown how the process can be partially automated using machine learning (ML). The field can be split into two areas: i) routing of bugs to human designers, and ii) localization of faults to specific parts of the software.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation